A Proposed Resistance-to-Time Converter with Switching Impulse Calibrators for Application in Resistive Bridge Sensors - M. Zahangir; Sheroz Khan; I. Adam; K. Abdul Kadir; A. N. Nordin; S. N. Ibrahim (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents a simple resistance-to-time converter. It consists of two voltage comparators, a ramp voltage generator, two logic gates and impulse voltage calibrators. A square-wave generator circuit is suggested in this paper. The design is simple and independent of the OPAMP offset issues. The resulting square-wave is rectified to get its DC equivalent and to a triangular output; the two outputs are applied to a comparator for generating a digital output with a duty cycle proportional to a change in resistance upon which is dependent the DC.